2013
DOI: 10.1002/pon.3273
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, wait‐list controlled trial: evaluation of a cognitive–behavioural group intervention on psycho‐sexual adjustment for men with localised prostate cancer

Abstract: This group-based CBT intervention for men post-radical prostatectomy for localised prostate cancer shows promising results in terms of improving quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Sexual satisfaction improved for patients in a combined online psycho‐educational intervention and moderated peer support forum . Only one trial improved multiple sexual outcomes; in addition to increased sexual QoL and orgasm satisfaction, Siddons et al reported increased masculine self‐esteem and sexual confidence for men treated with radical prostatectomy (90% ED) and who received a cognitive‐behavioural group intervention. Overall, 60% of trials reported follow‐up immediately following or close to intervention delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Sexual satisfaction improved for patients in a combined online psycho‐educational intervention and moderated peer support forum . Only one trial improved multiple sexual outcomes; in addition to increased sexual QoL and orgasm satisfaction, Siddons et al reported increased masculine self‐esteem and sexual confidence for men treated with radical prostatectomy (90% ED) and who received a cognitive‐behavioural group intervention. Overall, 60% of trials reported follow‐up immediately following or close to intervention delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Several psychosocial interventions have been developed which focus solely on addressing sexual dysfunction for men with prostate cancer (Brotto et al 2010, Siddons et al 2013) and it could be assumed that these interventions would be more successful in addressing participants' needs. They are, the topic of sexual dysfunction, the role of partners in CONNECT and intervention fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…Siddons, Wooten, and Costello (2013) conducted a randomized, wait-list control trial to evaluate a cognitive-behavioral therapy (CBT) group intervention to facilitate improved psycho-sexual adjustment to treatment side effects for PC survivors who had undergone RP [50]. A total of 60 men participated across nine cognitive behavioral groups, and completed a manualized 8-week cognitive-behavioral group intervention.…”
Section: Psychosocial Interventions For Ed Following Rpmentioning
confidence: 99%